Direct synthesis of 2, 5-diformylfuran from fructose with graphene oxide as a bifunctional and metal-free catalyst. Issue 8 (25th January 2016) - Lv, Guangqiang; Wang, Hongliang; Yang, Yongxing; Deng, Tiansheng; Chen, Chengmeng; Zhu, Yulei; Hou, Xianglin
Abstract : Graphene oxide, a metal-free carbon based material, was demonstrated to be an efficient and recyclable bifunctional catalyst in the direct synthesis of DFF from fructose. Abstract : The direct synthesis of 2, 5-diformylfuran (DFF) from fructose is a tandem reaction that typically involves two steps catalyzed by two different catalysts, including fructose dehydration to 5-hydroxymethylfurfural (HMF) catalyzed by an acid catalyst and subsequent HMF oxidation to DFF catalyzed by a redox catalyst. In this study, graphene oxide, a metal-free carbon based material, was demonstrated to be an efficient and recyclable bifunctional catalyst in the direct synthesis of DFF from fructose. A DFF yield of 53.0% was achieved in a one pot and one-step reaction (O2, 24 h) and the DFF yield could be further increased to 72.5% in a one pot and two-step reaction (N2, 2 h and O2 22 h).